GRAPHICAL METHODS FOR DEPICTING PRISMATIC CLOSED HELICAL SURFACES (PZVP) - Madumarov Komil Homitovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article proposes geometric and mathematical models of PVVP, allows the method of constructing a torus grid to perform images of a given model according to given parameters, and finds characteristic key determinants that enable the fundamental component of architectural shaping in CAD